Soggettività, identità nazionale, memorie Biografie e autobiografie nella Turchia contemporanea - BERTUCCELLI, Fulvio (Biblioteca di Studi di Filologia Moderna, 2017)
This volume aims at investigating the reasons why, in Turkey, individual memory and construction of subjectivity (both intended in the broad sense) go beyond the boundaries of the individual in order to incorporate matters concerning national identity. The "writings on the self", be them confessions, memoirs, autobiographical or biographical novels, have been chosen as tools for the comprehension of the construction mechanisms of individual and collective memory. The issues related to the building of the modern Turkish nation, with its traumatic historical events and the approaches to the theme of memory by those who were excluded from the dominant and hegemonic narrative, constitute the core themes around which the authors' reflection develops.